Software Quality is Multidimensional: Let's Play with Tensors - Neri, Hilmer R.; Travassos, Guilherme H. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
In the face of the dynamic nature of modern software systems, the quality of software products must be monitored and assured from different perspectives at the same time and throughout the development cycle. Although different characteristics and subcharacteristics can represent a software product quality, they have been historically studied and observed in a unidimensional way, which restricts the ability to observe the multiple relationships among quality characteristics. There is empirical evidence indicating the multidimensionality of this phenomenon. Therefore, an n-dimensional software quality base model is presented. The fundamentals of tensor algebra provide its basis, which explores the combination of different dimensions and relations of quality (internal, external, and in use) to suggest the level of quality of a software product. Preliminary results of its operationalization are presented to support this proposal.